The relationship between general policing attitudes and how officers perceive the potential advantages of body cameras - Kim, Dae-Young (Journal of crime and justice, 2021)
Many studies of police body cameras explored the officers’ attitudes towards their use. Much of this research examined the relationship between officers’ characteristics and their attitudes toward body cameras. Missing from the scholarship are measures of general policing attitudes and their impact on body camera attitudes. This study explored the possibility that officers’ positive attitudes toward body cameras are mediated by their outlooks toward law enforcement, perceptions of citizen cooperation, or levels of distrust of the public. A convenience sample of police officers from two Northeastern police agencies completed an online survey. Structural equation modeling indicates that officers with an orientation toward aggressive law enforcement are more likely to have a positive view of BWC effects on job performance and community relations. Officers with a positive outlook on citizen cooperation are more likely to have a positive view of BWC effects on job performance and community relations. Implications of these findings are discussed.